PENGARUH PEMBERIAN BOKASHI KAYAMBANG TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) PADA TANAH GAMBUT - Suriyani Suriyani; Zubaidah S.; Sulistiyanto Y.; Sustiyah Sustiyah (AgriPeat, 2015)
This study aims to determine the effect of giving kayambang bokashi (Salvinia molesta) on the growth of oil palm seedlings on peat. The research was conducted at land of Analytical laboratory Palangkaraya University, from July to October 2011. This research used Completely Randomized Design (CRD) single factor consisting of four treatments are: 0 ; 0,5; 1,0; and 2,0 kg. Bokashi kayambang polibag-1). Each treatment was repeated 6 times to obtain 24 units of the experiment. The results showed that bokashi kayambang has effect on height increment, increment the number of stem leaves and wet and dry weight of oil palm seedlings. There is no significantly different on stem diameter increment, leaf area, root length and number of roots. Bokashi kayambang a dose of 2 kg. Polybag-1 provides a real impact and can improve the wet and dry weight of oil palm seedlings